Electrical conductivity of different common bean seeds genotypes - Silva, Sibelle Santanna Da; Vieira, Roberval Daiton [UNESP]; Grzybowski, Camila Ribeiro De Souza; Carvalho, Tereza Cristina De; Panobianco, Maristela (ABRATES - Associação Brasileira de Tecnologia de Sementes, 2013)
The electrical conductivity test is a fast and non-subjective method used to assess seed physiological potential. Thus, the objective of this study was adapting the methodology for conducting the electrical conductivity test in common bean seeds and investigate effects of genotype in results of the test, comparing cultivars of the two trade groups: Carioca and Black. The study was conducted in two phases: 1- tests with combinations of different temperatures (20, 25, 30, and 35 °C) and five different inhibition periods (4, 8, 16, 20 and 24 h); and 2- assessment of influence of genotype by comparing results obtained on the seeds of both groups. Tests of accelerated aging and seedling emergence in field were also performed. It was concluded that, for seeds of common beans, electrical conductivity test may be performed with samples of 50 seeds per replication, soaked into 75 mL deionized water, incubated at 25 °C, and performing reading of results after 20 or 24 h. It was also concluded that test efficiency is variable according to genotype, and that for the trade group Carioca, there is not genotype effect; although the same results have not occurred for results obtained for the trade group Black.

O teste de condutividade elétrica é um método rápido e não subjetivo empregado na avaliação do potencial fisiológico de sementes. O objetivo deste trabalho foi adequar a metodologia para a condução do teste de condutividade elétrica em sementes de feijão, bem como investigar o efeito de genótipo nos resultados do teste, comparando cultivares de dois grupos comerciais: carioca e preto. A pesquisa foi conduzida em duas etapas: 1- testes com diferentes combinações de temperatura (20, 25, 30 e 35 °C) e período de embebição (4, 8, 16, 20 e 24 horas); e 2 - avaliação da influência do genótipo, comparando as sementes das cultivares dos dois grupos comerciais. Também foram conduzidos testes de envelhecimento acelerado e emergência de plântulas no campo. Conclui-se que, para sementes de feijão, o teste de condutividade elétrica pode ser conduzido com 50 sementes por repetição, embebidas em 75 mL de água deionizada, incubadas a 25 °C, com leitura após 20 ou 24 horas. Também se concluiu que a eficiência do teste é variável de acordo com o genótipo, e que, para o grupo comercial carioca, não há efeito de genótipo; embora o mesmo não tenha ocorrido para os resultados obtidos para o grupo comercial preto.
Condutividade elétrica de sementes de diferentes genótipos de feijão
Keywords: Phaseolus vulgaris; vigor; leaching; Phaseolus vulgaris; vigor; lixiviação